STRATEGY TO INCREASE TECHNOLOGY AWARENESS THROUGH THE USE OF VARIOUS DIGITAL MEDIA AMONG MADRASAH IBTIDAIYAH WONOMERTO TEACHERS - Maulidah, Qoifatul; Soliha, Imro Atus; Yulina Fadilah (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2025)
This research explores strategies to increase technological awareness among Madrasah Ibtidaiyah teachers in Wonomerto through the utilization of digital media. This research aims to fill the void of studies on teachers' technological awareness in the madrasah context by using a descriptive qualitative approach with a single case study design applied, involving observation, semi-structured interviews, and document analysis for two months (May-June 2025). Data were obtained directly through semi-structured interview techniques, open-ended questionnaires, and review of relevant documents, and then analyzed using an interactive model. The results show four main findings: First, awareness arising from practical needs in the classroom, second, the contribution of internal learning communities in accelerating technology adoption, third, structural challenges along with adaptive response mechanisms, and fourth, the insertion of Islamic values in digital materials. The findings show that the combination of collaborative practices, locally developed innovations and reinforcement of moral values plays an important role in building teachers' confidence in supporting the sustainable use of technology. In conclusion, the integration of these three elements forms the foundation for a resilient and effective digital learning ecosystem